Validation of a novel intermittent W' model for cycling using field data - Skiba, P. F.; Clarke, D.; Vanhatalo, A.; Jones, A. M. (International Journal of Sports Physiology and Performance, 2014)
Recently, an adaptation to the critical-power (CP) model was published, which permits the calculation of the balance of the work capacity available above the CP remaining (W'bal) at any time during intermittent exercise. As the model is now in use in both amateur and elite sport, the purpose of this investigation was to assess the validity of the W'bal model in the field. Data were collected from the bicycle power meters of 8 trained triathletes. W'bal was calculated and compared between files where subjects reported becoming prematurely exhausted during training or competition and files where the athletes successfully completed a difficult assigned task or race without becoming exhausted. Calculated W'bal was significantly different between the 2 conditions (P < .0001). The mean W'bal at exhaustion was 0.5 ± 1.3 kJ (95% CI = 0-0.9 kJ), whereas the minimum W'bal in the nonexhausted condition was 3.6 ± 2.0 kJ (95% CI = 2.1-4.0 kJ). Receiver-operator-characteristic (ROC) curve analysis indicated that the W'bal model is useful for identifying the point at which athletes are in danger of becoming exhausted (area under the ROC curve = .914, SE .05, 95% CI .82-1.0, P < .0001). The W'bal model may therefore represent a useful new development in assessing athlete fatigue state during training and racing.